Systematics and biogeography of the Boana albopunctata species group (Anura, Hylidae), with the description of two new species from Amazonia. Issue 4 (19th May 2021) - Fouquet, Antoine; Marinho, Pedro; Réjaud, Alexandre; Carvalho, Thiago R.; Caminer, Marcel A.; Jansen, Martin; Rainha, Raíssa N.; Rodrigues, Miguel T.; Werneck, Fernanda P.; Lima, Albertina P.; Hrbek, Tomas; Giaretta, Ariovaldo A.; et al.
Abstract : The outstanding species richness of Amazonia has fascinated biologists for centuries. However, the records of actual numbers and distribution of species forming its ecosystems are so incomplete that the understanding of the historical causes and regional determinants of this diversity remain speculative. Anuran clades have repeatedly been documented to harbour many unnamed species in this region, notably the Boana albopunctata species group. Considering the documented distribution and the ecology of the species of that group, we hypothesized that it diversified via successive trans-riverine dispersals during the late Miocene and Pliocene, after the formation of the modern Amazon watershed. To test this hypothesis, we gathered an extensive dataset of 16S rDNA sequences sampled throughout Amazonia and a mitogenomic dataset representative of the diversity of the clade to (1) re-evaluate species boundaries and distributions, and (2) infer the spatio-temporal history of diversification within Amazonia. We delimited 14 Operational Taxonomic Units (OTUs) in an Amazonian clade, i.e., 75% higher than currently recognized (14 OTUs for eight described species). Combining molecular data with morphological and acoustic data, two new species, Boana courtoisae sp. nov. from the eastern Guiana Shield and Boana eucharis sp. nov. from Southern Amazonia, are described herein. These species belong to a clade that diversified throughout Amazonia during the last 10 Ma, thus more recently than co-distributed small terrestrial anurans but concomitantly with other more vagile vertebrates. Our time-scaled phylogeny and biogeographic analyses suggest an initial east-west divergence and confirm reciprocal trans-riverine dispersals during the last 5 Ma. The geomorphological evolution of the region and species-specific dispersal ability largely explain these distinct spatio-temporal patterns across anurans. http://www.zoobank.org/zoobank.org:act:4F8ACA9F-F6F1-4605-BD6C-6D4650AACCBE http://www.zoobank.org/zoobank.org:act:51CC7B40-2D6B-4A9E-AF50-AB34D4CE1042